Total exchange routing on hierarchical dual-nets. (25th January 2015) - Li, Yamin; Chu, Wanming
The hierarchical dual-net (HDN) is a newly proposed interconnection network for building extra large scale supercomputers. The HDN is constructed based on a symmetric product graph (called base network), such as three-dimensional torus and n -dimensional hypercubes. A k -level hierarchical dual-net, HDN( B, k, S ), is obtained by applying k -time dual constructions on the base network B. S defines a supernode set that adjusts the scale of the system. The node degree of HDN( B, k, S ) is d 0 + k, where d 0 is the node degree of the base network. The HDN is node and edge symmetric and can contain huge number of nodes with small node-degree and short diameter. The total exchange, or all-to-all personalised communication, is one of the most dense communication patterns and is at the heart of numerous applications and programming models in parallel computing. In this paper, we show that the total exchange routing can be done on HDN efficiently and extra large scale HDNs can be implemented easily.